Simple Fertilizer Spreader to Improve Agricultural Productivity in Adireja Wetan Village - Nabila, Adinda Khasnania; Merlina, Merlina; Nuraeni, Fitria Sarah; Salsabila, Tyas Syifa; Mahiesa, Bio Hiero Al; Gandhi , Alvito Abby; Vauzi, Muhamad; Fadila, Farah Azzah; Aliahadi, Keizha Aura; Susanto, Yusup; Nurcahya, Melisa Eko; Mildaeni, Itsna Nurrahma; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This community service program was conducted by KKN Reguler UMP Group 121 in Adireja Wetan Village, Cilacap Regency, aiming to enhance fertilization efficiency and empower local farmers using Appropriate Technology (AT). The project involved designing, assembling, and implementing a simple PVC-based fertilizer spreader that is lightweight, durable, and easy to use. Before implementation, a needs analysis was conducted through interviews and field observations to identify challenges faced by farmers in manual fertilization methods. Participatory training sessions were held to teach farmers the correct usage, maintenance, and safety procedures of the tool. Field trials demonstrated that the fertilizer spreader improved the uniformity of fertilizer distribution, reduced labor intensity, minimized physical fatigue, and increased fertilization efficiency by approximately 30% compared to traditional methods. Feedback from farmers highlighted improved comfort, safety, and productivity during agricultural activities. This project shows that simple, low-cost technological innovations can significantly enhance agricultural productivity, support sustainable farming practices, and empower rural communities. The approach also emphasizes the importance of involving local farmers in every stage to ensure adoption, practicality, and long-term benefits., and long-term benefits.